Insufficient Zn uptake reduces rice grain yield in integrated rice-crayfish culture – a case study in the Jianghan Plain, China. Issue 6 (12th May 2023) - Gu, Sen; Zhou, Wei; Bai, Juan; Cheng, Peng; Bao, Xu; Jiao, Yang; Zhang, Tanglin; Li, Qingman
ABSTRACT: China has recently seen a substantial increase in integrated rice-crayfish ( Procambarus clarkii ) culture (IRCC). However, grain yield reductions (GYR) with rice plants having normal vegetative growth but failed filling are becoming common in IRCC, and the driving factors remain unclear. Here, we tried to identify the mechanisms behind this GYR mode in the Jianghan Plain, China, by investigating the soil properties, grain yield parameters, and plant mineral content in five IRCC plots experiencing GYR and an adjacent paddy-upland rotation plot (CK). The results showed slight to extreme GYR (11–82%) in the IRCC plots compared to those in CK. The translocation of phosphorus from shoot to grain during the productive stage of rice plants was inhibited in IRCC plots (26–71%) compared to CK (75%). The grain yield and phosphorus translocation coefficient correlated strongly (r > 0.95) with zinc uptake in aboveground rice organs which was significantly lower in IRCC than in CK. We conclude that this GYR in IRCC plots is not due to decreased macronutrients availability or heavy metals toxicity in IRCC soils, but the insufficient uptake of zinc by IRCC rice plants. We recommend Zn foliar spray or introducing Zn efficient rice cultivars as potential mitigation measures.